Clonal CD8+ T Lymphocytic Proliferation and Karyotypical Abnormalities in an EBV Associated Hemophagocytic Lymphohistiocytosis - Jiehao Zhou; Dehua Wang; Mehdi Nassiri (Hindawi Limited, 2015)
EBV associated hemophagocytic lymphohistiocytosis and EBV-positive T cell lymphoproliferative disease of childhood share many histologic and clinical features, which sometimes makes it very difficult to render a definitive diagnosis. In this report, we present a 16-year-old male who developed symptoms clinically consistent with EBV associated hematophagocytic lymphohistiocytosis including fulfilling most of HLH diagnostic criteria and responding promptly to HLH targeted therapy. However, histologic and cytogenetics features of this case are very concerning for EBV-positive T cell lymphoproliferative disease of childhood. This case demonstrates an ambiguous boundary of these two disease entities and emphasizes the importance of comprehensive evaluation and clinical correlation with cases suspicious of EBV driven hemophagocytic or lymphoproliferative process.